Aceites esenciales de orégano (Origanum vulgare L) y su efecto en parámetros de salud y productivos en pollos cobb 500 - Ganchozo Moreira, Walther Aldair (2019)
The objective of this research was to evaluate the effect of the addition of essential oils of oregano in Cobb 500 broilers on the productive and health parameters. A bifactorial arrangement was used, which included the effect of oregano essential oil in 3 doses (100, 200 and 300ppm) plus two control treatments, commercial oregano essential oil (250 g / t) and growth promoter antibiotic (APC) (300 g / t). For the study of the data, the analysis of the variance was used through the Statistix 8.0 and SAS 9.2 statistical packages and alpha value of 5%. Significant differences between sex and dose were observed in every week except for week two (P = 0.05), the treatment that reported the greatest weight gain in females (300 ppm) with 2596.1 (g), for weekly food consumption existed significant differences between sex-dose in week five (P <0.01), where the treatment that reported lower total consumption was (300 ppm) with 4.67 (Kg) of males. For the weekly nutritional conversion there were significant differences between sex-dose in week three (P <0.01). While for the immunological variables there were significant differences between the liver and gizzard organs in relation to sex at 21 days (P = 0.03), (P = 0.02) respectively. The results allow us to conclude that the addition of essential oils of oregano at the level of 200 ppm in males, and 300 ppm for females, obtained the highest production rates, and thus constitutes an alternative in the breeding of Coob 500 chickens.